PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS TERHADAP MAMBER SEKOLAH PAPAN BAITUL MUAMALAT PONDOK AL HIKMAH NGAWEN KECAMATAN BLORA DENGAN KEPUASAN SEBAGAI MODERASI - Rohwiyati, Rohwiyati; Harsono, Mugi (Universitas Of Surakarta, 2020)
In this study the authors have a goal to determine the influence of service quality as seen of tangibles, reliability, responsiveness, assurance and emphathy for member loyality, as well as moderating satisfaction in the effect of service quality on loyalty. Hypothesis in this research are: Suspected the service quality as seen of tangibles, reliability, responsiveness, assurance and emphathy have significan effect to member loyality, and satisfaction moderatedthe effect service quality as seen of tangibles, reliability, responsiveness, assurance and empathy to mamber loyalty, but satisfaction not mederated the effect service quality as seen of assurance and empathy to mamber loyalty. The data needed in this study is the primary data obtained by questionnaire method from the sample of 59 respondents. Data analysis used in this research is multiple linear regression test, t test, F test and coefficient of determination test. The results of data analysis in this study can be concluded that the service quality as seen of tangibles, reliability, responsiveness, assurance and emphathy have significan effect to member loyality, and satisfaction moderated the effect service quality as seen of tangibles, reliability, and responsiveness to mamber loyalty, but satisfaction not mederated the effect service quality as seen of assurance and empathy to mamber loyalty.